Comparative analysis of the interrelations between the stock, gold, and crude oil markets: Evidence from the Weimar Triangle countries - Mamcarz, Katarzyna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The paper aims to investigate and compare the relationships between the stock, gold, and crude oil markets as key financial assets in the Weimar Triangle countries. The markets of the Weimar Triangle member countries have not been previously considered and compared as a group of cooperating countries. The study covers a period of heightened volatility on commodity markets (gold, crude oil) due to the COVID-19 pandemic and the outbreak of the war in Ukraine. The methodology applied includes stationarity testing followed by the estimation of a vector error correction model to examine cointegration between asset prices and a test for the Granger causality in France, Germany, and Poland. The main findings indicate that stock returns Granger-cause crude oil returns in France, Germany, and Poland. However, a statistically significant correlation is observed only in France. Moreover, gold returns Granger-cause stock returns only in Poland, despite significant correlations in all countries. In contrast, the gold and the crude oil markets are independent. In the case of observed Granger causality, asset prices can be predicted based on the evolution of the prices of the other analysed assets. There exists cointegration of asset prices, with gold prices moving in the same direction as stock prices, and oil prices in the opposite direction in France and Germany, while in Poland the relationships are reversed. Cointegration implies that the prices of the analysed assets exhibit a tendency to return to equilibrium in the long run.